We Were Physcians - Eduardo, García-Solis (British Journal of Healthcare and Medical Research, 2023)
We were physicians, persons who prepared ourselves to give our best, to relieve the sick, not only physically but sometimes emotionally. At the present it has been written, conferences have been given, in relation to the dehumanization of medicine. The medicine trade. Physicians who charge $1500.00 (66 dollars) per consultation while the minimum wage is $172.87 (8 dollars), perhaps a medicine for the rich? That is why when we treat a patient, we are not satisfied with just making a good diagnosis and a timely treatment, let us do something more; like in a give and take, where the patient and the physician are amalgamated, let us shake hands with the patient and together let us walk the path with a deep human sense full of love and understanding for our patient. Our patient who is a human being who sometimes requires only a few words of encouragement. There is much more to do. This is where we are, we need the complicity and support of many other colleagues who, like me, miss being physicians in the true sense of the word. It is everyone's responsibility, especially medical educators, not to say we were physician but that we are physicians.